Two Sides of the Same Pill? Fertility Control and Mental Health Effects of the Contraceptive Pill - Valder, Franziska (Journal of Labor Economics, 2025)
I investigate the link between access to the contraceptive pill, mental health, education, and labor market outcomes. Liberalizing education and labor market effects of access to the pill via its fertility control function are well established. More recently, however, a medical literature suggests a link between hormonal contraception and depression. Exploiting variation in access to the pill, I document substantial mental health effects of the pill. These mental health effects are driven by individuals with a genetic predisposition for depression who then do not experience the positive effects on education and labor market outcomes.